Scientific evidence and guidelines in occupational medicine - Cristaudo, Alfonso (La Medicina del Lavoro, 2020)
In the past, science has had a conflicting relationship with the philosophy from which it has detached itself due to the scientific method of Galileo Galilei, but anti-scientific atti-tudes and thoughts still persist in every field of knowledge. Occupational Medicine, like other medical disciplines, increasingly needs to have a scientific foundation that guaran-tees evidence and appropriateness for its varied professional activities. Guidance tools for occupational physicians and, in particular, the Guidelines of Scientific Societies repre-sent an indispensable contribution to correct professional practice. In many countries, in addition to the International Society of Reference and International Commission of Occu-pational Health (ICOH), there are National Societies of Occupational Medicine and many of these, such as the Italian Society of Occupational Medicine, regularly publish policy tools and guidelines for the occupational physician. It is not always possible to base the Guidelines in the field of occupational medicine exclusively on consolidated scientific ev-idence but it is still necessary to increase research and publications aimed at evaluating the effectiveness of specific interventions in the preventive, clinical and rehabilitative field of occupational medicine in order to guide occupational physicians to an increasingly appropriate practice. In Italy, a recent law allows the production of Guidelines that partially exempt criminal lia-bility for inexperience through a System of Guidelines produced by accredited Scientific Societies.